Resistência genética à ferrugem-da-folha e ferrugem-docolmo nas variedades brasileiras de trigo Toropi e BRS - Coelho, Mônica Bossardi (2021)
Leaf rust (Puccinia triticina Erikss) (Pt) and stem rust (Puccinia graminis Pers. f. sp. tritici Eriks. & E. Henn) (Pgt) characterize important bottlenecks in wheat production throughout the world. As pathogens spread and develop new virulences, durable genetic resistance is the most effective control strategy. The Brazilian variety „Toropi‟ has maintained durable resistance to Pt for over 50 years, and has been studied and considered a valuable genetic resource for rust diseases. In addition to „Toropi‟, „BRS 194‟ variety, developed in 2000, was also resistant to all Pt races occurring in Brazil and in South American countries, until its qualitative resista nce was overcome five years later by a new Pt virulence, MFP-CT race. This study was carried out in two locations (Brazil and Canada) and aimed to investigate leaf and stem rust resistance in both varieties. A double-haploid population was developed from „Toropi‟ x „BRS 194‟ and inoculated in the seedling stage with the MCJ-HN (Pt) race in Brazil. In adult plant stage, the population was inoculated with MFP-CT (Pt) in Brazil and CCDS (Pt) in Canada. The population and parents were also genotyped for rye translocation 1BL.1RS, segment known to possess rust resistance genes, and for the presence of Sr36 gene. For stem rust, parental seedlings were inoculated with isolates TTKSK (Ug99), TPMK, TMRT, RHTS, MCCF, QTHJF and RTHJ. For leaf rust, in the seedling stage, „BRS 194‟ exhibited resistance (TI =; 1) and „Toropi‟ displayed susceptibility (TI = 3). The 1:1 proportion observed in the population indicated a single resistance gene from „BRS 194‟. In the adult plant test in Brazil with MFP-CT isolate, „BRS 194‟ ex hibited susceptibility (TI = 3) and „Toropi‟ showed resistance (TI = 0; / 0; 1). In the test carried out in Canada, „BRS 194‟ was susceptible (TI = 3) and „Toropi‟ resistant (IT = 1-). Regarding 1BL.1RS translocation, „Toropi‟ was negative and „BRS 194‟ was positive. „BRS 194‟ was resistant to all Pgt races, and IT=0 to TTKSK suggested the presence of gene Sr36, which was supported by molecular marker STM773-2 (+) and variety „Arthur 71‟ (Sr36 carrier) in its pedigree. The variety „Toropi‟ was resistant to RHTS, MCCF, QTHJF and RTHJ, suggesting that „Toropi‟ has a Pgt resistance gene. These results provide new perspectives regarding the Brazilian wheat varieties „Toropi‟ and „BRS 194‟. Both genotypes provide effective resistance sources against Pt and Pgt and are valuable for expanding the genetic base in wheat breeding programs. This study presents „BRS 194‟ as an adapted and resistant variety against Ug99, contributing for breeders to be at the forefront in the battle against this pathogen, which has not yet been detected in Brazil.